The evaluation of kops nut’s toxicity and antidiabetic properties: a pilot study - Johari, Liyana Nursyahirah (2023)
Diabetes mellitus (DM) is a metabolic disease resulting in uncontrollable elevation of the level of glucose in the blood. Ostodes pauciflora Merr. (Kop nuts) is a species from the family of Euphorbiaceae. which is known by local as ‘buah buantik’, ‘buah broti’ (Bidayuh community), and ‘buah merentik’ (Iban community). A few plants of the same genus have shown therapeutical effect against diseases such as leukaemia and cancer. O. pauciflora has been reported to contain bioactive compounds such as flavonoid and phenolic, which are known to contribute to the antidiabetic potential of a plant. Thus, a pilot study was designed to evaluate the hypoglycaemic properties of O. pauciflora oil extract on self-made high-fat diet (HFD) and streptozotocin (STZ) induced diabetic Sprague Dawley (SD) rats. α-amylase inhibition assays were conducted to assess the in vitro potential of Kops Nut's extract as an antidiabetic agent, while brine shrimp lethality assays (BSLA) were performed to gauge the toxicity of the extract. During the first 4 weeks, the experimental rats were given HFD to induce obesity, and injected with a single dose of STZ (35 mg/kg, intraperitoneal) on week 5 to induce diabetes (blood glucose >11 mmol/L). After 7 days of diabetes induction, the diabetic rats were given one dose of treatment of Kops Nut’s oil extract (hexane): 100 mg/kg, 200 mg/kg, and 400 mg/kg, respectively. The blood glucose-lowering effects were observed for 24 hours compared to the commercial medication, metformin (300 mg/kg). Among the extract concentrations tested, extract of 200 mg/kg was the most effective in lowering the blood glucose level within the 24-hour observing period comparable to metformin. α-amylase inhibition assay shows favourable results where hexane and diethyl ether extracts, have higher inhibitory activity compared to acarbose (positive control). BSLA result for hexane extract also come out as nontoxic as there were no mortality recorded. Therefore, from all the evidence collected in this study, O. pauciflora extracts might potentially lower the blood glucose level in T2DM rats.